Detection and quantification of lysine acetyl-alteration using antibody microarray. (November 2013) - Yao, Feina; Li, Ying; Yang, Pengyuan; Liu, Yinkun; Fan, Huizhi
Background: Lysine acetylation is a reversible and dynamic post-translational modification on proteins, and plays an important role in diverse biological processes. Technological limitations have so far prevented comparative quantification of lysine acetylation in different samples.Results: We developed a method to efficiently study lysine acetylation on individual proteins from complex mixtures, using antibody microarrays to capture individual proteins followed by detection with lysine acetyl antibody. By profiling both protein and acetylation variations in multiple samples using this microarray, we found cancer-associated lysine acetylation alteration on VEGF in the serum of hepatocellular carcinoma patients.Conclusion: Microarrays of lysine acetylation are highly effective for detecting acetylation, and should be useful in identifying and validating disease-associated acetylation alterations as biomarkers under both normal and pathological circumstances.